The Effect of Implementing an Educational Program Regarding Neurological Examination on Nurses at Asella Teaching and Referral Hospital in Oromia Region, Ethiopia: A Quasi-Experimental Study - Kandula UR; Teklewold E; Zemene Y; Begna D; Tuji TS (Dove Medical Press, 2022)
Usha Rani Kandula, Eshete Teklewold, Yoseph Zemene, Dinkinesh Begna, Techane Sisay Tuji Department of Clinical Nursing, College of Health Sciences, Arsi University, Asella, EthiopiaCorrespondence: Usha Rani Kandula, Department of clinical nursing, College of Health Sciences, Arsi University, Oromia Region, P.O. Box-396, Asella, Ethiopia, Tel +251-939052408, Email neha2010dec@gmail.com; usharani2020@arsiun.edu.etBackground: The central nervous system assessment is typically perceived as a complicated exam that would be both time-consuming and challenging. A disciplined approach and directed guidelines can ameliorate much of the difficulties involved. Nursing staff should have the required knowledge of neurological examination is intended to facilitate the physician in clinical check-ups, which would lead to the client’s enhanced well-being.Objective: The study’s goal is to determine the “Effect of implementing an educational program regarding neurological examination on nurses”.Methods: Quasi-experimental research work was carried out at Asella teaching referral hospitals in the Oromia Region of Ethiopia to assess the effect of implementing an educational program regarding neurological examination on nurses. To hand pick up 56 study samples, a convenient sampling technique was asserted. At first, a comprehension set of questions on neurological examination has been used to undertake a pre-measurement evaluation, which was accompanied by a two-week self-administered intervention in an educational program regarding the neurological examination. Followed that, the same comprehension set of questions on neurological examination was used for post-measurement evaluation among nursing professionals. The acquired data was entered into epi-info version-7 for coding and error prevention and transferred to SPSS version 22 for analysis employing descriptive and inferential statistics, and after the results of the research have been contextualized.Findings: The investigation outcomes showed that the pre-measurement mean and SD were 13.02± 2.62, while the post-measurement mean and SD were 22.63± 3.21. The paired-t-test resulted in t=26.24 (p=0.00, df-55, S*) for the effect of implementing an educational program regarding neurological examination among nurses. Whereas, linear multiple regression was explained with no statistically significant association between pre-measurement knowledge and the study’s demographic factors.Conclusion: The study strongly indicates that there is a significant effect of implementing an educational program regarding neurological examination among nurses.Keywords: effect, implementation, educational program, neurological examination, Nurses Oromia Region, Ethiopia